Analysis of 809 Facial Bone Fractures in a Pediatric and Adolescent Population - Kim, Sang Hun; Lee, Soo Hyang; Cho, Pil Dong (Archives of Plastic Surgery, 2012)
Background Facial fractures are infrequent in children and adolescents and have different clinical features from those in adults. The low incidence in children and adolescents reflects the flexibility and underdevelopment of their facial skeletons, as well as their more protected environments. Only a few reports have reviewed such patients in Korea. The authors performed a retrospective study to analyze the characteristics of facial fractures in the Korean pediatric population.Methods We conducted a retrospective review on a series of 741 patients, aged <18 years, with facial fractures who had been treated at our hospital between 2006 and 2010. The following parameters were evaluated: age, sex, cause, location and type of fractures, associated injuries, treatment and complications.Results A total of 741 consecutive patients met the inclusion criteria. The ratio of boys to girls was 5.7:1. Facial fractures most commonly occurred in patients between 13 and 15 years of age (36.3%). The most common causes of injury was violence. The nasal fracture was the most common type of fracture (69%) and the blowout fracture was the second most common (20%). Associated injuries occurred in 156 patients (21%).Conclusions The incidence of pediatric facial fractures caused by violence is high in Korea. Our results show that as age increases, etiological factors and fracture patterns gradually shift towards those found in adults. This study provides an overview of facial fractures in these age groups that helps illustrate the trends and characteristics of the fractures and may be helpful in further evaluation and management.
Keywords: Facial bones; Adolescent; Violence